2015
DOI: 10.1007/s12263-015-0501-3
|View full text |Cite
|
Sign up to set email alerts
|

Coffee provides a natural multitarget pharmacopeia against the hallmarks of cancer

Abstract: Coffee is the second most popular beverage in the world after water with a consumption of approximately two billion cups per day. Due to its low cost and ease of preparation, it is consumed in almost all countries and by all social classes of the population through different modes of preparation. Despites its simple appearance, a cup of coffee is in fact a complex mixture that contains hundreds of molecules, the composition and concentration of which vary widely and depend on factors including the origin of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 145 publications
(163 reference statements)
1
72
0
3
Order By: Relevance
“…Darker roasts contain a smaller amount of chlorogenic acids [16]. Hydroxyhydroquinone is a compound that is generated from the roasting of coffee beans [28]. Direct measurements of commercially available brewed coffee showed that less than 200 mg chlorogenic acids is generally contained in one serving [37].…”
Section: Test Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…Darker roasts contain a smaller amount of chlorogenic acids [16]. Hydroxyhydroquinone is a compound that is generated from the roasting of coffee beans [28]. Direct measurements of commercially available brewed coffee showed that less than 200 mg chlorogenic acids is generally contained in one serving [37].…”
Section: Test Beveragesmentioning
confidence: 99%
“…Coffee has a complex chemical mixture with hundreds of compounds. Roasting coffee results in the loss of chlorogenic acids and generation of hydroxyhydroquinone [28]. A previous study showed that hydroxyhydroquinone inhibits the chlorogenic acid-induced restoration of endothelial function in a rat model of hypertension [29].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products originated in marine and terrestrial organisms feature numerous chemical structures that modulate a wide range of biological effects. They have been used in traditional medicine for thousands of years without having a complete understanding of their mechanism of action [30]. Phytochemicals or phytonutrients are bioactive food constituents derived from a plant source; they intervene as inducers of important mechanisms related to antioxidant defense, longevity, cell maintenance, gene expression modulation and DNA repair [31].…”
Section: Chemoprevention In Lung Cancermentioning
confidence: 99%
“…A cup of coffee is a complex mixture containing more than a thousand molecules, heterogeneous bioactive compounds able to act on different cancer hallmarks, helping to prevent its appearance and development [30]. It has been demonstrated that daily drinking of 4-6 cups of regular black coffee, meaning up to 750 mL, is sufficient to prevent carcinogenesis and slow the progression of different types of cancer [33].…”
Section: Chemoprevention In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation